So-called “dangerous prisoners” – selected issues from the perspective of individual’s rights protection - Kotowska, Monika; Karaźniewicz, Justyna (Review of European and Comparative Law, 2022)
The issue of “dangerous” prisoners is of utmost importance, mainly regarding the restrictions imposed on offenders of this category. The restrictions in question introduce significant limitations of the statutory rights of individuals and alter the purposes of the penalty of deprivation of liberty. For this reason, it is necessary to align the Polish law, and above all penitentiary practice, with the international standards of human rights protection. This paper analyses both the Polish legislation and practice in terms of the qualification and treatment of “dangerous” prisoners . The paper points to the obscurity of certain legal regulations and the broad limits of discretion in applying and extending “dangerous prisoner” status. Furthermore, the paper evaluates the concept of distinguishing the category of “dangerous prisoners” and the operation of “N” wards from the perspective of the impact that such heightened isolation exerts on the individual, but also on the society and the penal institution .